The impact of socio-demographic, environmental, and individual factors on urban park visitation in Beijing, China. (1st October 2017) - Liu, Hongxiao; Li, Feng; Xu, Lianfang; Han, Baolong
Abstract: Urban parks improve quality of life by providing an array of cultural and natural ecosystem services, such as maintaining biodiversity, reducing air pollution, and benefiting residents' physical and mental states. Although government invests a large amount of capital into park management, parks are still underused in many cases. In this study, the association and relative importance of socio-demographic, environmental, and individual factors were investigated with regards to their impact on citizens' park visitation. Data was collected through cross-sectional door-to-door questionnaires and online databases, and was analyzed using a hierarchical regression model. Results showed that physical exercise (27.4% of collected reports) and rest and relaxation (26.7%) were the two most widespread reasons for park use. When asked about constraints of park visitation, time limitations were reported as being the most constraining factor. However, our quantitative analysis found no significant correlation. Socio-demographic, environmental, and individual variables explained 1%, 20% and 26% (adjusted R 2 ) of the total variance in frequency of park visitation between participants, respectively. A citizen's neighborhood greenspace, housing price, and distance from the nearest park were negatively correlated with park use. Among individual factors, a participant's reported affinity for park visits, time spent in their residential greenspace, and number of children under seven were positively correlated with park visitation, with a decreasingβcoefficient. This research highlights the predominant contribution of attitude over accessibility factors when it comes to park visitation. Furthermore, the data indicates that accessibility factors function differently for frequent, infrequent, and moderate park users and provision with parks within 1000 m of their home is recommended. The findings have implications for park management and future research.